Consumers' Acceptance to Buy and Dispose of Recycling Textile Products - Alsayed, Roa (AUC Knowledge Fountain, 2024)
The textile industry is the second most polluting worldwide, following food manufacturing. It is one of the industries that is rarely scrutinized in the Middle East and North Africa (MENA) region. This work analyzes the fashion industry from the perspective of consumer attitudes towards the purchase and disposal of clothing, and their behavior with regards to old garments. The study was conducted in Saudi Arabia and Egypt, two countries that achieved similar results in the fashion industry. The methodology is divided into three phases. First, the manuscript begins with a review of topics such as sustainability, consumer behavior in the fashion sector, and sustainable fashion as an innovation by highlighting some industrial applications in other countries. This secondary research demonstrated that textile recycling works in other countries and has the potential to succeed in the MENA region. The second phase includes interviews with industry experts, managers, and site visits. Lastly, consumer interviews were conducted as a focus phase. Content analysis as an exploratory tool was used to analyze the results of the interviews. It was demonstrated that both countries were in the early stages of recycling textile waste, but they had the motivation to enter this market. Also, it showed that the pressure coming from governments were the main purpose of implementing this kind of projects. KSA and Egypt were similar from the perspective of culture, and that was shown in consumer interviews in how they deal with their old garments. In the end, it was concluded that only customers can control the power of the market.